Respiratory Diseases' Burden in children and adolescents of marginalized population: A retrospective study in slum area of Karachi, Pakistan - Sharif, Hina; Jan, Shah Sumaya; Sharif, Sana; Seemi, Tooba; Naeem, Hira; Rehman, Junaid (Frontiers in Epidemiology, 2023)
Background: Worldwide, the burden of respiratory disease has dramatically increased, endangering public health. To our knowledge, there have been no reported cases of respiratory illness among children and adolescents living in the slums of Karachi, Pakistan. This study aimed to assess the burden of respiratory disease in marginalized slum populations, and the factors causing such increase in the burden. Methods: This study was conducted in 35 slums of Karachi, Pakistan to determine the prevalence of respiratory disease in children and adolescents. Data on pneumonia, bronchitis, bronchiolitis, tuberculosis, and asthma from August 2019 to July 2022 was analyzed and inferences drawn. Results: Among the studied diseases, pneumonia was more prevalent among females 39864 (44.9%), followed by males 19006 (21.4%). Most, 59988(67.6%) of the children were from 1- 5 yrs. Also, of those diagnosed with pneumonia, 50348(56.8%) were from the same age group. Furthermore, bronchiolitis was found among 10830(12.2%) children aged 5-9 yrs old. The majority, 46906(52.9%) of the studied population, belonged to the Pathan ethnicity, followed by Sindhi 21522(24.2%), and most of them, 84330(95.1%), belonged to lower socioeconomic status. Conclusions: This study found that pneumonia is most common respiratory disease followed by bronchiolitis in children and adolescents in marginalized slum population of Karachi, Pakistan. Both pneumonia and bronchiolitis have seasonal variations in their occurrence.